Ex post impact assessment of agricultural research in subSaharan Africa: the IITA experience - Nkamleu, G.B.; Coulibaly, O.; Sanogo, D.; Manyong, Victor M.; Alene, Arega D. (2007)
The International Institute of Tropical Agriculture (IITA) and its research-for-development partners have made substantial contributions to food security, poverty reduction and environmental protection in sub-Saharan Africa. Technologies developed and largely diffused include high yielding varieties (cassava, cowpea, yam, maize, soybean, plantainbanana), Integrated Pest Management of varieties resistant and tolerant to pests and diseases, biological control of pests and alien invasive species, eco-friendly biopesticides, improved crops, natural resource and postharvest management practices. IITA has also a sound track record in capacity building of partners including farmers, the public and private sectors, field and laboratory technicians, NGOs, national agricultural research scientists, and rural development project managers. This review highlights a few case studies of ex post and ex postex ante impact assessment, using time series and cross-section data of some of these technologies, and finds a significant contribution to productivity, incomes, genderequity, and nutrition at household, farm, community, country, and regional levels. It makes recommendations for strategies for a higher diffusion of the technologies through access to input and output markets and a sound partnership between research and development including a private-public partnership to achieve the highest returns on agricultural research investments.